A comparative study on the Chinese consumers' perceptions towards Western and Chinese fashion bloggers in the luxury products industry - Piliu, A. (2017)
Purpose – The aim of this dissertation is to provide an understanding of the perceptions of the Chinese female consumers concerning both the Western and Chinese female fashion bloggers in the Luxury product Industry.